2021
DOI: 10.3390/children8020058
|View full text |Cite
|
Sign up to set email alerts
|

Can Event-Related Potentials Evoked by Heel Lance Assess Pain Processing in Neonates? A Systematic Review

Abstract: To clarify the possibility of event-related potential (ERP) evoked by heel lance in neonates as an index of pain assessment, knowledge acquired by and problems of the methods used in studies on ERP evoked by heel lance in neonates were systematically reviewed, including knowledge about Aδ and C fibers responding to noxious stimuli and Aβ fibers responding to non-noxious stimuli. Of the 863 reports searched, 19 were selected for the final analysis. The following points were identified as problems for ERP evoked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 101 publications
0
2
1
Order By: Relevance
“…The application of ERPs evoked by heel lance as an assessment tool for neonatal pain has been the topic of a recent systematic review 26. While it has been suggested that ERP evoked by heel lance may be a reflection of the activation of Aβ fibres responding to non-noxious stimuli and not the activation of Aδ or C fibres responding to noxious stimulation, we found a distinct difference in the ERP-based response to vibration compared with skin puncture in our study.…”
Section: Discussioncontrasting
confidence: 66%
“…The application of ERPs evoked by heel lance as an assessment tool for neonatal pain has been the topic of a recent systematic review 26. While it has been suggested that ERP evoked by heel lance may be a reflection of the activation of Aβ fibres responding to non-noxious stimuli and not the activation of Aδ or C fibres responding to noxious stimulation, we found a distinct difference in the ERP-based response to vibration compared with skin puncture in our study.…”
Section: Discussioncontrasting
confidence: 66%
“…However, this index leaves doubts about the research results. In neonates, the ERP evoked by skin puncture in the heel (heel lance) consists of N2P2 and N3P3 waves, and the N3P3 is considered an ERP specific to heel lance (Shiroshita et al, 2021). The N3P3 latency has been reported as 420 ms (Slater et al, 2010b), 383 ms (Verriotis et al, 2016), and 403 ms (Fabrizi et al, 2016) for N3, and as 560 ms (Slater et al, 2010b), 554 ms (Verriotis et al, 2016), and 538 ms (Fabrizi et al, 2016) for P3.…”
Section: Introductionmentioning
confidence: 99%
“…IES, as an alternative to laser stimulation, avoids limitations such as skin overheating and lesions due to repeated laser stimulation; moreover, it can selectively activate nociceptive Aδ and C fibers in the epidermal layer of the skin when low stimulation current intensities are applied (Inui et al, 2002;Mouraux, Iannetti & Plaghki, 2010). However, the exact latency evoked by the activation of Aδ and C fibers in neonates remains unknown, and whether the ERP evoked by heel lance in neonates reflects activation of Aδ or C fiber is yet to be determined (Shiroshita et al, 2021).…”
Section: Introductionmentioning
confidence: 99%